Micropezidae (Insecta, Diptera, Acalyptratae) of Madagascar and a revision of the genus Paramimegralla Hennig - Marshall, Stephen A. (Zootaxa, 2017)
The Micropezidae of Madagascar are reviewed, and the endemic genus Paramimegralla Hennig is revised. Twenty species are recognized including two Hybobata species and 18 Paramimegralla species, of which 12 are described as new (P. luteoscapus, brunnea, zinzala, zarpa, verticalis, taeniola, sulcata, campanula, anchivitta, quadrifasciata and longicephala). Stiltissima Barraclough is synonymized with Paramimegralla Hennig and previous records of Rainieria Rondani from the island are shown to be incorrect. Paramimegralla steineri (Barraclough) and Paramimegralla volcanica (Barraclough) are given as new combinations, Paramimegralla stuckenbergi Barraclough is synonymized with P. nigra Barraclough, and Hybobata Enderlein is resurrected from synonymy with Mimegralla Rondani. All known Malagasy micropezid species are keyed and illustrated and all Paramimegralla species are described or redescribed.